Smart Transportation Systems 2022 Proceedings of 5th KES-STS International Symposium - Bie, Yiming; Qu, Bob X.; Howlett, Robert J.; Jain, Lakhmi C.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book gathers selected papers presented at the KES International Symposium on Smart Transportation Systems (KES STS 2022). Modern transportation systems have undergone a rapid transformation in recent years, producing a range of technological innovations such as connected vehicles, self-driving cars, electric vehicles, Hyperloop, and even flying cars, and with them, fundamental changes in transport systems around the world. The book discusses current challenges, innovations, and breakthroughs in smart transportation systems, as well as transport infrastructure modeling, safety analysis, freeway operations, intersection analysis, and other related cutting-edge topics.
Keywords: Transportation engineering; Traffic engineering; Engineering$1 (BData processing.s; Artificial intelligence; Transportation Technology and Traffic Engineering; Data Engineering; Artificial Intelligence; Intelligent transportation systems -- Congresses; Transportation -- Data processing -- Congresses